معوقات استخدام الوسائل التعليمية في المدارس الابتدائية من وجهة نظر المعلمين ببلدية المسيلة - عشب, خليصة; ربيحة, بلاعدة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
This study aims to identify the level of obstacles to the use of educational aids in primary schools in the municipality of m'sila.to achieve the objectives of this study، a five graded questionnaire was developed، which consisted in its final from (47) items distributed over (5) domains. they are obstacles related to the teachers، obstacles related to the learner، obstacles related to the educational means، obstacles related to the classroom environment، obstacles related to the educational and administrative system.this study was applied to a sample of (90) male and female teachers، this research rlied on the descriptive approach. After applying the study and conducting statistical treatment، the results showed that the level of obstacles to the use of educational aids in primary schools in the municipality of m'sila was average، where the area of obstacles related to the classroom environment and the educational administrative system was high، while the area of obstacles related to each of the educational means، the teacher and the learner، respectively، was medium تهدف هذه الدراسة إلى التعرف على مستوى معوقات استخدام الوسائل التعليمية في المدارس الإبتدائية ببلدية المسيلة، ولتحقيق أهداف هذه الدراسة تم تطوير استبانة ذات تدرج خماسي تكونت في صورتها النهائية من (47) فقرة موزعة على (05) مجالات هي: معوقات تتعلق بالمعلم، معوقات تتعلق بالمتعلم، معوقات تتعلق بالوسائل الوسائل التعليمية، معوقات تتعلق بالبيئة الصفية، معوقات تتعلق بالنظام التعليمي و الإداري. حيث طبقت هذه الدراسة على عينة قوامها (90) معلما ومعلمة وقد اعتمد هذا البحث على المنهج الوصفي. وبعد تطبيق الدراسة، وإجراء المعالجة الإحصائية اظهرت النتائج أن مستوى معوقات استخدام الوسائل التعليمية في المدارس الإبتدائية ببلدية المسيلة متوسط ، حيث كان مجال المعوقات التي تتعلق بالبيئة الصفية والنظام التعليمي و الإداريمرتفع، بينما مجال المعوقات التي تتعلق بكل من: الوسائل التعليمية و المعلم و المتعلم على التوالي متوسط.
Keywords: obstacles، educational means معوقات، الوسائل التعليمية